Behavior responses and survival of snakehead fish (Channa striata) broodstock during acclimatization - Aziz, Nurul; Prayitno, Slamet Budi; Haditomo, Alfabetian Harjuno Condro; Yuniarti, Tristiana; Hastuti, Sri; R. Eliver, Eirnest Dave Son (Departemen Akuakultur FPIK UNDIP, 2026)
Post-transport acclimatization is a critical phase in broodstock management, particularly for stress sensitive species such as snakehead fish (Channa striata). This study evaluated behavioral responses, feeding activity, and survival of snakehead broodstock during the first 24 hours of acclimatization following transport. The study employed a descriptive exploratory design using nine acclimatization units, with behavioral exploration conducted at two time points immediately after stocking (T0) and 24 hours post-stocking (T24). Behavior responses recorded included erratic swimming, hitting against walls, jumping, gasping, and rubbing, which were quantified during a 10 minute exploration period. Feeding response and survival rate were assessed at T24, while water quality parameters were monitored throughout the acclimatization period.The results showed that all behaviors responses were prominently expressed at T0, indicating acute stress responses following transport and handling. After 24 hours of acclimatization, a general reduction in the frequency of erratic swimming, hitting against walls, jumping, and rubbing was observed, suggesting partial behavioral recovery and adaptation to the new environment. In contrast, gasping behavior persisted with relatively minor changes, indicating that respiratory adjustment may require a longer recovery period. Feeding responses emerged in several acclimatization units at T24. Survival rates during the first 24 hours ranged from 80% to 100%, with an overall survival rate of approximately 92%. Water quality remained within tolerable ranges for Channa striata and was not considered a primary factor of behavioral variation or mortality. These results indicate that the first 24 hours post-transport represent a critical phase characterized by behavioral responses. Behavioral indicators, combined with feeding response and survival, provide a practical and non-invasive approach to assessing acclimatization success and fish welfare during the early post-transport period in snakehead broodstock